Apolipoprotein E ε4 and cognitive function after surgery in middle-aged and elderly Danish twins. Issue 11 (November 2020) - Dokkedal, Unni; Wod, Mette; Thinggaard, Mikael; Hansen, Tom G.; Rasmussen, Lars S.; Christensen, Kaare; Mengel-From, Jonas
Abstract : BACKGROUND: Transient cognitive impairment is common in adult patients of all ages following anaesthesia and surgery. Apolipoprotein E (APOE) ε4 carriers may have a larger deterioration in short-term cognitive function after major surgery compared with APOE ε4 noncarriers. OBJECTIVES: The aim was to examine the effect of APOE ε4 on the association between exposure to surgery and anaesthesia, and subsequent cognitive functioning. A more pronounced deterioration in cognitive function in APOE ε4 carriers was hypothesised. DESIGN: An observational cross-sectional and a 6 to 10 years longitudinal twin cohort design. SETTING: Survey and register study of 2936 Danish twins aged 45 to 92 years. MAIN OUTCOME MEASURES: Cognitive function was assessed using five age-sensitive cognitive tests. In the cross-sectional study, we compared twins exposed to surgery with a reference group (unexposed). Linear regression models were used adjusting for sex and age and stratified by APOE ε4 carrier status. In the longitudinal cognitive follow-up study 1671 twins participated. Intrapair analyses were also performed using 70 same-sexed twin pairs concordant for APOE ε4 carrier status, but discordant for major surgery. RESULTS: APOE ε4 carriers had lower cognitive scores compared with noncarriers, and this was statistically significant in elderly twins 70+ years of age (mean difference, −0.67; 95% CI, −1.14 to −0.17). There was no significant impact on cognitive function after surgery according to APOE ε4 carrier status in the cross-sectional study. Similarly, there was no APOE ε4 modification in the longitudinal study. Also, in the intrapair analyses no evidence was found of lower cognitive score after major surgery compared with the nonexposed cotwins among APOE ε4 carriers. CONCLUSION: No evidence was found of more pronounced long-term deterioration in cognitive function after surgery among APOE ε4 carriers, but elderly APOE ε4 carriers in general performed worse on the cognitive tests than noncarriers. Abstract : Supplemental Digital Content is available in the text